ON THE CONCEPT OF THE ENHANCED FON CATALOG COMPILATION - Andruk, V.; Yuldoshev, Q.; Eglitis, I.; Pakuliak, L.; Mullo-Abdolov, A.; Vaviliva, I.; Protsyuk, Yu.; Relke, H.; Golovnia, V.; Shatokhina, S.; Yizhakevych, O.; Ehgamberdiev, Sh.; et al. (Одеські астрономічні публікації, 2017)
We suppose to compile the enhanced version of FON (Photographic Survey of the Northern Sky) catalog of stellar positions and B-magnitudes in the sky region from -20 to 90 degrees on declination. The photographic base of the project comprises about 5,700 plates obtained at three observatories of the former SU MAO NAS of Ukraine, Kitab observatoryof Uzbekistan and Gissar observatory of Tajikistan. The mean epoch of the catalog is around 1988. The expected limited stellar magnitude is 17.5m. More than 5,400 plates are processed to support the photometric part of the catalog. The plates were shot on the 1.2 m Schmidt telescope in Baldone, Latvia, in the U and V bands. Color data provide the possibility ofcatalog correction for the photometric color equation. Stars brighter than V < 8.5m will be supplemented with photoelectric U, B, V data. Proper motions will be obtained using GAIA data.